1995
DOI: 10.1177/001789699505400302
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion in the high street: a study of community pharmacy

Abstract: Health promotion activity in community pharmacies was studied along with pharmacists' perceptions of the barriers and constraints to increasing health promotion activity within community pharmacy. A stratified sample (of 30 pharmacists) was investigated using a structured interview in the spring of 1993. Health promotion activities were undertaken by all study pharmacies. The number of times advice was given and/or a query dealt with was estimated to be around 1400 per week for the sample. It was found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…[35] Time limitations acted as a barrier to the pharmacists' MI use, consistent with previous research, which has also identified time as an important constraint for the health promotion role of pharmacists. [2,27] Considering the time constraints, pharmacy premises are more suitable for counselling in brief encounters rather than regular MI sessions, which typically last for 15 min (although this can vary widely). [11] The Behaviour Change Counselling model has been proposed as a simpler alternative to MI when contextual circumstances make MI use difficult.…”
Section: Discussionmentioning
confidence: 99%
“…[35] Time limitations acted as a barrier to the pharmacists' MI use, consistent with previous research, which has also identified time as an important constraint for the health promotion role of pharmacists. [2,27] Considering the time constraints, pharmacy premises are more suitable for counselling in brief encounters rather than regular MI sessions, which typically last for 15 min (although this can vary widely). [11] The Behaviour Change Counselling model has been proposed as a simpler alternative to MI when contextual circumstances make MI use difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to health promotion in pharmacies that have been suggested previously can be overcome. 17 Previous studies specify the barriers as being: (i) no liaison with other primary care team members, (ii) lack of space, (iii) lack of finance from health authority and (iv) lack of courses.…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacists' self-reported levels of health promotion activity in a South London health authority were studied using structured interviews with a stratified sample of 30 pharmacists in1993. 9 All the pharmacists reported that they undertook health promotion activities. Proactive advice was estimated to be given about 398 Transparency Ð evidence must include a clear and transparent account of how it was collated, which sources of information have been consulted, who was involved in collating the evidence, how the work was funded, a full disclosure of any analysis and findings Systematicity Ð evidence identified must display clearly, regardless of the individual study, report or review methodology, the process through which the evidence was gathered and assessed Relevance Ð evidence must be judged to be relevant to health development, and in this instance to the role of community pharmacy times a week for the sample.…”
Section: Pharmacists' Perceptions Of Current and Potential Involvementmentioning
confidence: 99%